2010
DOI: 10.1186/1471-2164-11-376
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome analysis of a livestock-associated methicillin-resistant Staphylococcus aureus ST398 isolate from a case of human endocarditis

Abstract: BackgroundRecently, a new livestock-associated methicillin-resistant Staphylococcus aureus (MRSA) Sequence Type 398 (ST398) isolate has emerged worldwide. Although there have been reports of invasive disease in humans, MRSA ST398 colonization is much more common in livestock and demonstrates especially high prevalence rates in pigs and calves. The aim of this study was to compare the genome sequence of an ST398 MRSA isolate with other S. aureus genomes in order to identify genetic traits that may explain the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
160
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(173 citation statements)
references
References 44 publications
12
160
1
Order By: Relevance
“…For livestock CC398 (sequenced by Schijffelen et al, 2010, andUhlemann et al, 2012), our study demonstrated that this clade has undergone a host transition from originally humans to animals, mainly pigs and calves (van Loo et al, 2007;Lewis et al, 2008). However, as the present study demonstrates, CC398 is also a pathogen of bovine IMI.…”
Section: Clonality Of Bovine Strains and Phylogeneticscontrasting
confidence: 40%
“…For livestock CC398 (sequenced by Schijffelen et al, 2010, andUhlemann et al, 2012), our study demonstrated that this clade has undergone a host transition from originally humans to animals, mainly pigs and calves (van Loo et al, 2007;Lewis et al, 2008). However, as the present study demonstrates, CC398 is also a pathogen of bovine IMI.…”
Section: Clonality Of Bovine Strains and Phylogeneticscontrasting
confidence: 40%
“…However, phage endopeptidases, for example lysostaphin which is capable of degrading some human proteins, may affect mammalian tissues (Park et al, 1999). This possibility could be investigated with an animal model of endocarditis for example, as CC398 isolates have been associated with a human case of endocarditis in a highly immuno-compromised patient (Schijffelen et al, 2010). However, the two subgroups of isolates recovered from human invasive infections (those harboring StauST398-4pro and those harboring StauST398-4pro and StauST398-5pro) did not differ in their ability to invade human cells, suggesting that the StauST3985-pro prophage is not involved.…”
Section: Discussionmentioning
confidence: 99%
“…LA CC398 isolates commonly carry phages /2 and / 6 (Schijffelen et al, 2010;Hallin et al, 2011;McCarthy et al, 2011), or a /Avb prophage (Price et al, 2012). By contrast, isolates belonging to the human clade contain b-converting /3 prophage variants that encode two immune-modulating proteins (Goerke et al, 2006;McCarthy et al, 2011;Price et al, 2012;Uhleman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sequences within subfamilies shared 94 to 100% ANI, whereas sequences from different subfamilies shared 69 to 81% ANI. The S. aureus strains ED98 (25) and S0385 (26) each carried multiple subfamilies of ICE6013 (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%